Predicting mental motivation in terms of some artistic gymnastics skills for students of the College of Physical Education and Sports Sciences - م.م علا سلام غازي; أ.د. هدى عبد السميع (physical education and sport sciences college for women/ Baghdad University, 2021)
The importance of the research lies in trying to identify these variables and to know the relationship between mental motivation and the performance of some artistic gymnastics skills for students of the College of Physical Education and Sports Sciences. The problem of the research is that learning skills in any game or activity does not depend only on the physical and technical side, but the psychological aspect has a great role. In her learning, and with this, the researchers noticed that the educational process depends mainly on physical, technical and psychological interdependence, and through the researchers' experience of being specialized in and informing her of these lessons, they found that the psychological aspect is not included in the educational units used in the curriculum for most of the professor in the Faculties of Physical Education and Sports Sciences in Iraq Which reflects negatively on the preparation of students from the psychological side, especially in the variable of mental motivation that must be characterized by each student. One of the aims of the research is to identify the mental motivation and performance of some artistic gymnastics skills for students of the College of Physical Education and Sports Sciences. The two researchers used the descriptive approach in the method of survey study and correlational relations, and a community of students of the third phase in the College of Physical Education and Sports Sciences at the University of Kufa for the academic year 2020-2021 were identified and their number (56) students, then a sample consisting of (30) students was chosen in order to apply the scale and the tests. On them, and appropriate statistical treatments were used to reach the results, after which the results were presented, analyzed and discussed, and the two researchers reached conclusions, including that there is a direct relationship between mental motivation and the performance of your artistic gymnastics skills for students of the College of Physical Education and Sports Sciences, and the greater the mental motivation, the higher the performance of your artistic gymnastics skills For students of the College of Physical Education and Sports Sciences, and based on these conclusions the two researchers made a set of recommendations, including the necessity of using and applying the mental motivation scale and performance tests of some artistic gymnastics skills for students of the College of Physical Education and Sports Sciences for their benefit in assessing and preparing good students.